Pembelajaran Water Rescue sebagai Tanggap Awal Keselamatan Menghadapi Banjir bagi Karang Taruna Kecamatan Benjeng, Kabupaten Gresik - Yandika Fefrian Rosmi; Riga Mardhika; Santika Rentika Hadi; Ujang Rohman; Sumardi Sumardi; Ahmad Nuryadi (Jurnal Pengabdian Pada Masyarakat, 2020)
WATER RESCUE LEARNING AS AN INITIAL RESPONSE TO SAFETY AGAINST FLOODS FOR YOUTH ORGANIZATION IN BENJENG DISTRICT, GRESIK REGENCY. Disasters are events that are not expected by many people, need special anticipations in overcoming this. Not only is the SAR team needed as a response team from the start but the community participation is also needed to take part in it. Benjeng District, which is a subscribed area for floods, naturally initiates knowledge and skills regarding disaster response. Based on this, the Physical Education Lecturer team of the University of PGRI Adibuana Surabaya carried out the activity as a lecturer task in the field of Higher Education Tri Dharma, namely Community Service. The purpose of this activity is to increase knowledge and ways to save water by members of the Youth Organization. There were 36 participants in the workshop. The results that can be obtained from the workshop are 1). The high level of enthusiasm of the participants gave a positive impact so that the achievements designed by the team were successfully completed well; 2). The implementation of the workshop activities resulted in a pioneer team of emergency response that would be destroyed at the village level so that it became the vanguard of the rescue team in the event of a flood.